THE IMPOVERISHED AND THEIR ENTITLEMENT TO ADEQUATE HOUSING: A SYNTHETIC ANALYSIS - DAVID KUMIJE; ABUBAKAR ZUBAIRU AGUYE (International Studies Journal)
Poverty is a worldwide issue that affects people from all walks of life, regardless of their race, gender, religion, or continent. It is a significant challenge that hinders and destroys the beauty of human existence. Governments and countries worldwide are taking various actions to tackle this endemic malaise; however, the more significant the efforts to alleviate poverty's impact, the harder it becomes. The most exacerbated blows of poverty's consequences are deprivation to adequate housing. This paper aims to explore the relationship between poverty and the challenge the poor face to secure adequate shelter in Nigeria. Shelter is a crucial key among the basic necessities of life, and it is one of the fundamental rights recognized by many constitutions worldwide. Content analysis of relevant legal instruments and literature was employed as a research methodology. Using the Structural Inequality Theory which examines how social, economic, and political structures contribute to unequal distribution of resources, opportunities, and power among different groups in society the study found that although access to adequate shelter is a fundamental human right, the poor in Nigeria are far from enjoying this inalienable right. The paper therefore, recommended among others that the government in partnership with the private sector should evolve a pragmatic approach, including policies to promote affordable housing, combat discrimination, and ensure legal protections for the poor.